ACETYLSALICYLIC ACID TREATMENT IN WASTEWATER BY ELECTROCOAGULATION USING ALUMINUM ELECTRODES: ELECTRICAL VOLTAGE EFFECT - Falcón, Ángel José de la Cruz; Bergamasco, Rosangela; Theodoro, Joseane Debora Peruço; Rios, Magaly de la Cruz; Marques, Thiago Andrade; Domingos, Artur Veloso; Colher, Cristiano António (Seven Editora, 2024)
Electrocoagulation is a technique that uses electric current to induce oxidation-reduction reactions, forming hydroxides that act as coagulating agents for the removal of emerging contaminants. The general objective of this study is to evaluate the efficiency of the electrocoagulation process applied to the treatment of emerging contaminant acetylsalicylic acid by electrocoagulation. Emerging pollutants are chemicals, both natural and synthetic, and can be organic and inorganic, with high toxic potential and negative impacts on both the environment and human health. A factorial design of 33 times in triplicate was developed, the important variables were reaction time and electrical voltage. The dependent variables or response were concentration and operating cost. At the end of the treatments, the results indicated that the highest percentage of acetylsalicylic acid elimination at 5 volts was 58.67% in the total times of 10, 20 and 30 minutes at the initial concentration of 0.3 mg/mL. In the 11-volt tests, the best removal efficiency was 60.00%, with 30 minutes of removal time. As expected, the greatest wear of the electrodes was obtained through the tests subjected to 11 volts, and in relation to the cost of operation, the test with the highest cost was R$ 3.15/m3. For tests subjected to 5 Volts, the highest cost was R$ 0.73/m3. The results of the study indicated significant elimination of aspirin. Therefore, this study can be a reference for other researchers or manufacturers to evaluate and estimate the process on a larger scale using this system for the treatment of synthetic wastewater.DOI: https://doi.org/10.56238/sevened2024.037-117